A Study of Rural Marketing in India with Special Reference to Villages in Western Uttar Pradesh (International Journal of Innovative Research in Engineering & Management, 2022)
Companies are always willing to capture  new markets and thus they tried to made things available  to the villages and developed an infrastructure of supply  chain. The media habits of rural consumers have a large  influence on the effectiveness of rural marketing. Though  all forms of media are used in rural areas, audiovisual  media such as radio, television, and films are especially  important due to low literacy rates. As a result, most  marketers prefer mass media to reach rural audiences;  however, mass media, while effective in urban areas,  cannot be as effective in rural areas. This is primarily due  to a lack of electricity and linguistic diversity. Before  developing a communication package to deliver the  product message to rural audiences, it is critical to understand the aspirations, fears, and hopes of rural  customers in relation to each product category. Earlier  rural market which was limited to agricultural products  mainly now has been a market for so many goods.
Keywords: Rural Market segment; Villages market potential; marketing